Mobile Greenhouse Test Facility Design for Analogue Testing at the German Neumayer III Antarctic Station - Zabel, Paul; Bamsey, Matthew; Schubert, Daniel; Poulet, Lucie; Zeidler, Conrad (2014)
Technologies for deployment into a mobile plant production unit are presently undergoing test at the German Aerospace Center’s Institute for Space Systems. Developing subsystems include LED lighting, aeroponic nutrient delivery, ion-selective sensors and stacked growth systems. These systems will soon be integrated into a sea-container to undergo an integrated test-campaign prior to the eventual deployment to the Antarctic. The high yield, low resource use plant production system will be installed externally to the nominal Neumayer III station and operate year-round. Produced food will provide non-negligible supplementation to over-wintering crew diets enhancing the psychological well-being of crew members. The Alfred Wegner Institute’s Neumayer III Antarctic station, serves as a useful space analogue site for the advancement of several key technologies and general operational strategies of space-based bio-regenerative life support systems. Due to the integrated nature of the mobile test facility, quantification of all inputs, generated biomass and crew time will be conducted. Although primary operations will be conducted by the Neumayer III crew members, in an analogous manner to on-orbit and future planetary surface plant production systems, telepresence by a backroom of experts will also be incorporated into the overall greenhouse operational strategy. Results of a survey of other past and current Antarctic greenhouses and growth chambers will also be described.